Early Sport Specialization and Intensive Training in Adolescent Female Athletes: Risks and Recommendations. Issue 5 (October 2017) - Blagrove, Richard C.; Bruinvels, Georgie; Read, Paul
Abstract : ABSTRACT: EARLY SPORT SPECIALIZATION IS OFTEN CHARACTERIZED BY INTENSIVE TRAINING AND IS BECOMING INCREASINGLY COMMON. ADOLESCENT FEMALE ATHLETES, WHO TRAIN EXCESSIVELY AND ADOPT POOR DIETS, ARE AT RISK OF THE FEMALE ATHLETE TRIAD, OVERUSE INJURY, MENTAL HEALTH ISSUES, AND OVERTRAINING. THE OCCURRENCE OF ONE OR MORE OF THESE ISSUES CAN LEAD TO EARLY RETIREMENT FROM SPORT AND MAY HAVE SERIOUS LONG-TERM HEALTH CONSEQUENCES. PRACTITIONERS WORKING WITH YOUNG FEMALES ARE RECOMMENDED TO ADOPT A HOLISTIC APPROACH TO THE DEVELOPMENT OF THEIR ATHLETES, INCLUDING PARTICIPATION IN A DIVERSE RANGE OF SPORTS, MONITORING HEALTH STATUS, AND ENSURING CALORIC INTAKE MEETS THE DEMANDS OF THE ATHLETE'S LIFESTYLE.